Structure of Relationships Between the University Organizational Image and Student Loyalty - Álvarez-García, José; del Río-Rama, María de la Cruz; Oliveira, Cristiana; Durán-Sánchez, Amador (Frontiers in Psychology, 2021)
The aim of this research is to contrast an explanatory model of how the perceived organizational image of a university center (faculty) influences its students' loyalty. The data is obtained from a structured survey of students in Spain, obtaining a sample of 224 valid questionnaires. The methodology used is exploratory and confirmatory factor analysis to validate the measurement scales and the estimation of the model is carried out by applying Structural Equation Modeling (SEM). The results show that organizational image is the key variable to influence students' decision to continue taking new courses at the center, as well as to recommend it to other people. It is observed that the greater students' positive perception of the organizational image is, the greater their satisfaction with the center will be, which results in a higher level of loyalty to the center in which they study. However, their identification levels with the center is not a relevant variable in the process of increasing loyalty.